2021
DOI: 10.1001/jamanetworkopen.2021.8373
|View full text |Cite
|
Sign up to set email alerts
|

Overuse of Cervical Cancer Screening Tests Among Women With Average Risk in the United States From 2013 to 2014

Abstract: Key Points Question How often are cervical cancer screening tests overused in women with average risk in the United States? Findings In this cohort study of 2 299 177 commercially insured women aged 30 to 65 years who underwent cervical cancer screening in 2013 through 2014, 64.7% underwent repeat testing within 36 months of index testing. Meaning These findings suggest that despite evidence-based guidelines, overuse of cervical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 34 publications
2
36
1
Order By: Relevance
“…This study noted a similar disparity for breast cancer screening with mammography 26 . We found that women who did not undergo cervical cancer screening were unlikely to undergo a routine gynaecological examination, a finding previously reported in women with commercial insurance 10 . Although the value of an annual gynaecological examination has been the subject of debate, the findings further highlight the potential for disengagement from the healthcare system if cervical cancer screening is not routinely performed 27–30 .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This study noted a similar disparity for breast cancer screening with mammography 26 . We found that women who did not undergo cervical cancer screening were unlikely to undergo a routine gynaecological examination, a finding previously reported in women with commercial insurance 10 . Although the value of an annual gynaecological examination has been the subject of debate, the findings further highlight the potential for disengagement from the healthcare system if cervical cancer screening is not routinely performed 27–30 .…”
Section: Discussionsupporting
confidence: 78%
“…10 A previous analysis of women with commercial insurance noted that nearly two-thirds of women were over-screened with repeat testing within 3 years compared with the 33% of Medicaid beneficiaries noted in the current analysis. 10 Several factors probably contribute to the differential in overscreening. Medicaid beneficiaries have a poorer connection | 1109 to the medical system compared with insured women and therefore have potentially fewer interactions with providers in which screening tests may be offered.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“… 10 , 35 The American Cancer Society recommends the HPV test as the preferred primary screening method for cervical cancer for women 25 to 65 years of age. 36 Alternatively, individuals can be screened simultaneously with both the HPV and Pap tests (cotesting). Screening using HPV tests can be conducted less frequently than Pap tests ( i.e., every 5 years instead of three), decreasing the number of procedures and potential harm, including vaginal bleeding, pain, infections, and distress, throughout the lifetime of a patient.…”
Section: Early Detection For the Preventive Care Of Hpv-related Cancermentioning
confidence: 99%
“…Screening using HPV tests can be conducted less frequently than Pap tests ( i.e., every 5 years instead of three), decreasing the number of procedures and potential harm, including vaginal bleeding, pain, infections, and distress, throughout the lifetime of a patient. 6 , 32 , 36 …”
Section: Early Detection For the Preventive Care Of Hpv-related Cancermentioning
confidence: 99%